Maternal and perinatal risk factors associated with neonatal asphyxia: a case–control study - I Gusti Agung Ayu Sriningrat; Sanjiwani , Made Indira Dianti; Suryaningsih , Putu Siska; Suryawan , I Wayan Bikin (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Neonatal asphyxia remains a major cause of neonatal morbidity and mortality worldwide and continues to be the second leading cause of neonatal death in Indonesia. Although numerous studies have examined maternal and perinatal risk factors, contemporary evidence from Bali particularly from Wangaya General Hospital remains limited. Objective: To analyze maternal and perinatal factors associated with neonatal asphyxia among newborns delivered at Wangaya General Hospital, Denpasar. Methods: An analytical case–control study was conducted using hospital delivery records from January to November 2024. A total of 189 newborns were included, consisting of 95 asphyxia cases and 94 non-asphyxia controls selected through proportionate stratified random sampling. Maternal variables (parity, hypertensive disorders, anemia, premature rupture of membranes) and perinatal variables (mode of delivery, gestational age, birth weight) were extracted from medical records. Associations were examined using odds ratios (OR) with 95% confidence intervals, followed by multivariable logistic regression to identify independent predictors of neonatal asphyxia. Results: Low birth weight (LBW) demonstrated the strongest association with neonatal asphyxia (adjusted OR = 112.66; 95% CI: 30.84–411.60; p < 0.001). Prematurity showed a significant crude association but became attenuated after adjustment, likely due to multicollinearity with LBW. Maternal factors including parity, hypertensive disorders, anemia, and premature rupture of membranes as well as mode of delivery did not show statistically significant associations in either bivariate or multivariable analysis. Conclusion: Neonatal asphyxia at Wangaya General Hospital is predominantly associated with perinatal biological vulnerabilities, particularly low birth weight and, to a lesser extent, prematurity. Maternal factors contributed minimally in this setting, suggesting that fetal maturity and neonatal physiological readiness play a more crucial role than maternal comorbidities. Strengthening antenatal strategies to prevent fetal growth restriction and enhancing preparedness for the stabilization of LBW and preterm infants are essential to reducing asphyxia-related morbidity.